Genetic Diversity and Population Structure of Medemia argun (Mart.) Wurttenb. ex H.Wendl. Based on Genome-Wide Markers - Elshibli, Sakina; Korpelainen, Helena (Frontiers in Ecology and Evolution, 2021)
Medemia argun is a wild, dioecious palm, adapted to the harsh arid environment of the Nubian Desert in Sudan and southern Egypt. There is a concern about its conservation status, since little is known about its distribution, abundance and genetic variation. M. argun grows on the floodplains of seasonal rivers (wadis). The continuing loss of suitable habitats in the Nubian Desert is threatening the survival of this species. We analyzed the genetic diversity, population genetic structure and occurrence of M. argun populations to foster the development of conservation strategies for M. argun. Genotyping-by-sequencing analyses were performed using a whole genome profiling service. We found an overall low genetic diversity and moderate genetic structuring based on 40 SNP (Single Nucleotide Polymorphisms) and 9866 SilicoDArT markers. The expected heterozygosity of the total population (HT) equaled 0.036 and 0.127, and genetic differentiation among populations/groups (FST) was 0.052 and 0.092, based on SNP and SilicoDArT markers, respectively. Bayesian clustering analyses defined five genetic clusters that did not display any ancestral gene flow among each other. Based on SilicoDArT markers, the results of the analysis of molecular variance (AMOVA) confirmed the previously observed genetic differentiation among generation groups (23%; p<0.01). Pairwise FST values indicated a genetic gap between old and young individuals. The observed low genetic diversity, and its loss among generation groups, even under the detected high gene flow, show genetically vulnerable M. argun populations in the Nubian Desert in Sudan. To enrich and maintain genetic variability in these populations, conservation plans are required, include collection of seed material from genetically diverse populations and development of ex situ gene banks.